The Role of DOT1L in Normal and Malignant Hematopoiesis - Arnold, Olivia; Barbosa, Karina; Deshpande, Aniruddha J.; Zhu, Nan (Frontiers in Cell and Developmental Biology, 2022)
Disruptor of telomeric silencing 1 (DOT1) was first identified in yeast (DOT1p) and is the sole methyltransferase responsible for histone three lysine 79 (H3K79) mono-, di-, and tri-methylation. Mammalian DOT1 (DOT1-like protein or DOT1L) has been implicated in many cellular processes, such as cell cycle progression, DNA damage response, and development. A notable developmental process reliant on DOT1L function is normal hematopoiesis, as DOT1L knockout leads to impairment in blood lineage formation. Aberrant activity of DOT1L has been implicated in hematopoietic malignancies as well, especially those with high expression of the homeobox (HOX) genes, as genetic or pharmacological DOT1L inhibition causes defects in leukemic transformation and maintenance. Recent studies have uncovered methyltransferase-independent functions and a novel mechanism of DOT1L function. Here, we summarize the roles of DOT1L in normal and malignant hematopoiesis and the potential mechanism behind DOT1L function in hematopoiesis, in light of recent discoveries.